2007
DOI: 10.1152/ajplung.00192.2007
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in airway responsiveness to sex hormones in rabbits

Abstract: TO THE EDITOR: Recently, Massaro and Massaro (4) demonstrated a sexual dimorphism of alveolar size in male and female adult rats and mice and that estrogen receptor (ER)-␣ and ER-␤ are required for this sexual dimorphism.Our group recently showed that a similar phenomenon of sexual dimorphism presents in airway responsiveness to sex hormones in rabbits. We studied the direct effect of sex hormones (testosterone and 17␤-estradiol) on airway smooth muscle (ASM) at rest and precontracted with acetylcholine or car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 4 publications
0
7
0
2
Order By: Relevance
“…In rabbit trachea testosterone relaxes precontracted ASM in an epithelium-dependent way 41 Gender differences in the incidence of asthma Testosterone serum levels are depressed in patients with respiratory failure, 76 cystic fibrosis, 77 hypoxic pulmonary fibrosis 78 and COPD 79…”
Section: Gendermentioning
confidence: 99%
See 2 more Smart Citations
“…In rabbit trachea testosterone relaxes precontracted ASM in an epithelium-dependent way 41 Gender differences in the incidence of asthma Testosterone serum levels are depressed in patients with respiratory failure, 76 cystic fibrosis, 77 hypoxic pulmonary fibrosis 78 and COPD 79…”
Section: Gendermentioning
confidence: 99%
“…Immunohistochemistry studies show that ASM obtained from male rabbits express classical androgen 41 and estrogens receptors. 42 Similarly, immunofluorescence experiments performed in our laboratory revealed that rabbit ASM cells express Androgen Receptors (ARs).…”
Section: Agementioning
confidence: 99%
See 1 more Smart Citation
“…Μελέτες που έγιναν σε ΛΜΙ τραχείας ενήλικων άρρενων κουνελιών φάνηκε ότι η τεστοστερόνη επιδρά άμεσα στην ανταποκρισιμότητα των ΛΜΙ των αεραγωγών με τρόπο εξαρτώμενο από το επιθήλιο και την παραγωγή ΝΟ [81,82] . Συγκεκριμένα προκαλεί δοσοεξαρτώμενη σύσπαση σε ημικρίκια τραχείας ενήλικων άρρενων κουνελιών και δοσοεξαρτώμενη χάλαση όταν σε αυτά έχουμε προτύτερα επιδράσει με ACh και καρβαχόλη (CCh) ενώ δεν έχει καμμία επίδραση σε ιστό θηλυκών κουνελιών.…”
Section: ο λειτουργικός ρόλος του επιθηλίουunclassified
“…Η μηχανική αφαίρεση του επιθηλίου εξουδετερώνει σημαντικά την δράση της χάλασης της ορμόνης. Αντίθετα η δράση χάλασης σε προσυσπασμένα ημικρίκια τραχείας ενήλικων άρρενων κουνελιών της 17β-οιστραδιόλης είναι ανεξάρτητη της παρουσίας επιθηλίου [82,83] .…”
Section: ο λειτουργικός ρόλος του επιθηλίουunclassified